Desain Media PAKAR (Papan Ular Tangga Kocok Arisan) Materi Pembagian di Sekolah Dasar - Yekti Arum Mubarok; Agus Sutono; Achmad Buchori (Lembaga Teewan Journal Solutions, 2026)
This research aimed to design PAKAR (Papan Ular Tangga Kocok Arisan) learning media for division material in elementary schools. The study was motivated by students’ low interest and difficulties in understanding division concepts in mathematics learning. This research applied the Research and Development (R&D) method using the ADDIE model, limited to the stages of Analysis, Design, and Development. The participants consisted of 28 fourth-grade students and one classroom teacher at SDN Kambangan 04, Lebaksiu District, Tegal Regency, five fourth-grade elementary school teachers in Tegal Regency, and two expert validators from Universitas PGRI Semarang. Data were collected through interviews, observations, needs questionnaires, and expert validation sheets. The findings indicated that students and teachers urgently needed innovative and interactive mathematics learning media. The PAKAR media was designed by integrating snakes and ladders games with lottery activities to create joyful and student-centered learning experiences based on constructivist theory. Expert validation results showed that the media was highly valid, with a score of 92.8 from the content expert and 94.7 from the construction expert. Therefore, the PAKAR media is considered highly feasible for implementation in elementary mathematics learning, particularly in division material.